2018
DOI: 10.3389/fpls.2018.01376
|View full text |Cite
|
Sign up to set email alerts
|

Extremophiles as a Model of a Natural Ecosystem: Transcriptional Coordination of Genes Reveals Distinct Selective Responses of Plants Under Climate Change Scenarios

Abstract: The goal of this research was to generate networks of co-expressed genes to explore the genomic responses of Rhizophora mangle L. populations to contrasting environments and to use gene network analysis to investigate their capacity for adaptation in the face of historical and future perturbations and climatic changes. RNA sequencing data were generated for R. mangle samples collected under field conditions from contrasting climate zones in the equatorial and subtropical regions of Brazil. A gene co-expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 104 publications
(115 reference statements)
3
11
0
Order By: Relevance
“…These results corroborate the findings reported by Cruz et al (2020), who performed a functional characterization of putative loci under selection and suggested that differential precipitation regimes play a fundamental role in genetic divergence between populations of this species. Additionally, our findings support the results reported by Bajay et al (2018), who found different profiles of gene expression among populations of Rhizophora mangle located at contrasting latitudes of the Brazilian coast, with differentially expressed genes putatively involved in the responses to variations in temperature, solar radiation, precipitation and flood frequency. The results obtained for both species corroborate the data from other studies reporting that precipitation and air and sea temperature variables are limiting factors regulating the distribution of coastal species (McKee et al, 2012;Soares et al, 2012;Osland et al, 2016;Duke et al, 2017;Cavanaugh et al, 2018;Ximenes et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…These results corroborate the findings reported by Cruz et al (2020), who performed a functional characterization of putative loci under selection and suggested that differential precipitation regimes play a fundamental role in genetic divergence between populations of this species. Additionally, our findings support the results reported by Bajay et al (2018), who found different profiles of gene expression among populations of Rhizophora mangle located at contrasting latitudes of the Brazilian coast, with differentially expressed genes putatively involved in the responses to variations in temperature, solar radiation, precipitation and flood frequency. The results obtained for both species corroborate the data from other studies reporting that precipitation and air and sea temperature variables are limiting factors regulating the distribution of coastal species (McKee et al, 2012;Soares et al, 2012;Osland et al, 2016;Duke et al, 2017;Cavanaugh et al, 2018;Ximenes et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…A completely different approach could be to focus on pathways and genes that are unique to a multifactorial stress combination [31]. An additional strategy could be to identify and study plants that are subjected to extreme and multifactorial stress conditions in nature (e.g., desert plants, plants growing under harsh conditions in industrial waste sites, salt marshes, and/or next to hot springs, and/or some invasive species) [84][85][86], and…”
Section: How Can We Develop Plants With Enhanced Tolerance To Multifamentioning
confidence: 99%
“…KcTrxf reduces stomatal aperture and promotes stomatal closure to retain water balance in leaves to overcome drought conditions ( Jing et al., 2020 ). Heat shock protein expression induced in response to oxidative stress is also correlated with induction of stomatal closure as acclimatization to heat stress ( Bajay et al., 2018 ). Sooner or later, the stress-driven changes in stomatal opening and closure upset photosynthesis in the leaves.…”
Section: Genetic and Molecular Basis Of Mangrove Adaptations To Intertidal Environmentsmentioning
confidence: 99%
“…In conjunction with stomatal closure, cuticles act as a barrier to water loss and the genes related to cuticle formation are clustered with that of oxidative stress response ( Bajay et al., 2018 ). 3-Ketoacyl-CoA synthase is the key gene involved in cutin, suberin, and wax formation which is highly expressed in K. obovata ( Su et al., 2019 ).…”
Section: Genetic and Molecular Basis Of Mangrove Adaptations To Intertidal Environmentsmentioning
confidence: 99%
See 1 more Smart Citation